Behavioral modeling of integrated phase-change photonic devices for neuromorphic computing applications - Carrillo, Santiago G.-C.; Gemo, Emanuele; Li, Xuan; Youngblood, Nathan; Katumba, Andrew; Bienstman, Peter; Pernice, Wolfram; Bhaskaran, Harish; Wright, C. David (APL Materials, 2019)
The combination of phase-change materials and integrated photonics has led to the development of new forms of all-optical devices, including photonic memories, arithmetic and logic processors, and synaptic and neuronal mimics. Such devices can be readily fabricated into photonic integrated circuits, so potentially delivering large-scale all-optical arithmetic-logic units and neuromorphic processing chips. To facilitate in the design and optimization of such large-scale systems, and to aid in the understanding of device and system performance, fast yet accurate computer models are needed. Here, we describe the development of a behavioral modeling tool that meets such requirements, being capable of essentially instantaneous modeling of the write, erase, and readout performance of various integrated phase-change photonic devices, including those for synaptic and neuronal mimics.
Keywords: Behavioral modeling; Integrated phase-change; Photonic devices; Neuromorphic computing applications